A monetary history of the Ottoman Empire - Pamuk, Şevket (Cambridge University Press, 1999)
The Ottoman empire stood at the crossroads of intercontinental trade at the dawn of the era of capitalism. This volume examines the monetary history of that empire from its beginnings in the fourteenth century to the end of the first world war. Through a detailed examination of the currencies and related institutions of an empire which stretched from the Balkans through Anatolia, Syria, Egypt and the Gulf to the Maghrib, the book demonstrates the complexity of the monetary arrangements and their evolution in response to both local developments and global economic forces. The volume also affords some valuable insights into social and political history and the evolution of Ottoman institutions. This is an important book by one of the most distinguished economic historians in the field.